2021
DOI: 10.1002/ctm2.324
|View full text |Cite
|
Sign up to set email alerts
|

IL‐22‐mediated renal metabolic reprogramming via PFKFB3 to treat kidney injury

Abstract: Kidney damage initiates the deteriorating metabolic states in tubule cells that lead to the development of end‐stage renal disease (ESTD). Interleukin‐22 (IL‐22) is an effective therapeutic antidote for kidney injury via promoting kidney recovery, but little is known about the underlying molecular mechanisms. Here, we first provide evidence that IL‐22 attenuates kidney injury via metabolic reprogramming of renal tubular epithelial cells (TECs). Specifically, our data suggest that IL‐22 regulates mitochondrial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Moreover, research suggests that MCL mitigates the severity of liver steatosis by enhancing autophagy and attenuating NF-κB-mediated inflammation ( Zhong et al, 2018 ). Additionally, it has been reported that resveratrol can inhibit the activation of the NLRP3 inflammasome by inducing autophagy, which ameliorates IgA nephropathy ( Wu et al, 2020 ; Chen et al, 2021 ). Considering this evidence, we speculated that MCL may alleviate radiation-induced pyroptosis by promoting autophagy and subsequently inhibiting the activation of the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research suggests that MCL mitigates the severity of liver steatosis by enhancing autophagy and attenuating NF-κB-mediated inflammation ( Zhong et al, 2018 ). Additionally, it has been reported that resveratrol can inhibit the activation of the NLRP3 inflammasome by inducing autophagy, which ameliorates IgA nephropathy ( Wu et al, 2020 ; Chen et al, 2021 ). Considering this evidence, we speculated that MCL may alleviate radiation-induced pyroptosis by promoting autophagy and subsequently inhibiting the activation of the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, according to the safety evaluations tests, the rapid DNA vaccination strategy showed an excellent safety. Chen et al found that the immune system, including IL-22, was closely related to the recovery of kidney and liver (46)(47)(48). These results inspire us that DNA cancer vaccine is an effect cancer treatment with good safety.…”
Section: Discussionmentioning
confidence: 95%
“…APAP-induced acute liver injury induces the expression of proinflammatory factors (such as IL-1β, IL-6, and TNF-α), which can then exacerbate organ damage, especially cause hepatocyte injury to damage the liver (Chen et al, 2020;Raevens et al, 2020;Saad et al, 2020;Chen et al, 2021). Therefore, inflammatory response is considered one of the basic mechanisms of APAP-induced liver injury (Huang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%